Virtual Build Design of Simulator Soldering - Ahmaddul Hadi; Muhammad Zuharmando Ghaffara; Noval Yusri Yandi; Khairi Budayawan; Bayu Ramadhani Fajri (Universitas Negeri Padang, 2021)
Electronic devices used by humans are often damaged. solder is the solution for repairing electronic devices. If someone wants to learn to use solder, they must study independently by watching video tutorials, when practiced without supervision is quite dangerous and this has a direct impact on workplace safety. The purpose of this research is to produce a Virtual Reality soldering application. Several stages were carried out in making this Virtual Reality soldering application, including analysis, design, development, and validation tests. The analysis is carried out by several processes including system requirements analysis and material analysis. In designing applications and creating virtual reality applications, Unity software is used as a game engine, and blender software is used to create 3-dimensional object assets. The results of the expert validation test of the virtual solder simulator media from the aspects of media design, software, and benefits obtained a score of 77.